(untitled) (International Journal of Engineering and Computer Science, 2017)
This system is based on fatigue detection using smartphone. Drowsiness of the driver will be detected by this system when the driver is driving the vehicle. Alert will be generated when a reverie is detected by the system. To detect the reverie some parameter are consider such as yawning, eyes blinking and head shaking. The Harr-like technique is used for detecting face expression and eye’s blinking. And for detecting yawning the Canny Active Contour method is used.